The influence of the cross-border innovation environment on innovation processes in agri-food enterprises – a case study from the Dutch-German Rhine-Waal region. Issue 1 (31st December 2023) - Neuberger, Sabine; Darr, Dietrich; Oude Lansink, Alfons G.J.M.; Saatkamp, Helmut W.
ABSTRACT: Enterprises of the agri-food and other sectors develop innovations that can serve the EU's Green Deal objective to become climate-neutral by 2050. Innovation processes face specific innovation environment conditions, which are beyond the enterprise's control. Our research aims to investigate how the innovation environment affects product innovation processes of agri-food enterprises located in a cross-border region. We developed our conceptual framework of the "cross-border innovation environment" based on innovation system and innovation management literature. We conducted semi-structured interviews in selected agri-food enterprises in the Dutch-German region Rhine-Waal. Results indicate that agri-food enterprises' innovation environments concentrated on national-level factors, and that cross-border factors and relationships were rare. Moreover, different factors influenced different stages of innovation processes that were primarily driven by markets compared to research. We conclude that integrating customers and business partners during research and technological development is important to address current challenges of the Green Deal. Understanding how the innovation environment influences innovation processes in agri-food enterprises can help to develop appropriate policies.